TIGA CARA MENENTUKAN NAMA WUKU DALAM PAWUKON SAKA - Agung Prabowo; Sugiyanto Sugiyanto; Indar Tri Wahyuni (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2015)
This article discusses Pawukon Saka which is a mathematical calendar.This article explains mathematical knowledge required to create Pawukon Saka and particularly called as Javanese Mathematics. The Pawukon Saka Calendar obtained is then used to check some calendars sculpted on various epigraphs using The Chinese Remainder Problem. There are some mistakes in the names of wuku sculpted on some epigraphs after checking.